IL-4 and IL-13 Receptor Signaling From 4PS to Insulin Receptor Substrate 2: There and Back Again, a Historical View - Keegan, Achsah D.; Zamorano, Jose; Keselman, Aleksander; Heller, Nicola M. (Frontiers in Immunology, 2018)
In this historical perspective, written in honor of Dr. William E. Paul, we describe the initial discovery of one of the dominant substrates for tyrosine phosphorylation stimulated by IL-4. We further describe how this “IL-4-induced phosphorylated substrate” (4PS) was characterized as a member of the insulin receptor substrate (IRS) family of large adaptor proteins that link IL-4 and insulin receptors to activation of the PI 3’ kinase pathway as well as other downstream signaling pathways. The relative contribution of the 4PS/IRS pathway to the early models of IL-4-induced proliferation and suppression of apoptosis are compared to our more recent understanding of the complex interplay between positive and negative regulatory pathways emanating from members of the IRS family.